The Companion to Language Assessment 2013
DOI: 10.1002/9781118411360.wbcla083
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Assisted Language Testing

Abstract: Technological advancements that occurred since the late 1980s have revolutionized many aspects of human life including second language (L2) education. Language learners and teachers are now presented with a plethora of technology‐enhanced instructional materials and resources varying from simple electronic dictionaries to full‐fledged online language programs. The ubiquity of technology has also affected language assessment and engendered the field of computer‐assisted language testing (CALT), dedicated to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Podstawą teoretyczną podejścia dydaktycznego założonego w tym układzie glottodydaktycznym jest testowanie komputerowe na odległość (web-based asssessment -Roever, 2001;Almond, Steinberg, Mislevy, 2002;Choi, Sung Kim, Boo, 2003) z analizą statystyczną wyników oraz elementami testowania adaptacyjnego (computer-adaptive assessment -por. Noijons, 2001;Ockey, 2009), kontynuujące długą tradycję wykorzystania technologii komputerowych w ocenianiu (Chapelle, Douglas, 2006;Douglas, Hegelheimer, 2007) i dostarczania rozszerzonej elektronicznej informacji zwrotnej (Cotos, 2011;Suvorov, Hegelheimer, 2014). Kursy na platformie WebClass są podzielone na dwa moduły -materiały oraz testy.…”
Section: Platforma Listig W Rozwijaniu Poprawności Językowej Na Potrzeby Glottodydaktyki I Transladydaktykiunclassified
“…Podstawą teoretyczną podejścia dydaktycznego założonego w tym układzie glottodydaktycznym jest testowanie komputerowe na odległość (web-based asssessment -Roever, 2001;Almond, Steinberg, Mislevy, 2002;Choi, Sung Kim, Boo, 2003) z analizą statystyczną wyników oraz elementami testowania adaptacyjnego (computer-adaptive assessment -por. Noijons, 2001;Ockey, 2009), kontynuujące długą tradycję wykorzystania technologii komputerowych w ocenianiu (Chapelle, Douglas, 2006;Douglas, Hegelheimer, 2007) i dostarczania rozszerzonej elektronicznej informacji zwrotnej (Cotos, 2011;Suvorov, Hegelheimer, 2014). Kursy na platformie WebClass są podzielone na dwa moduły -materiały oraz testy.…”
Section: Platforma Listig W Rozwijaniu Poprawności Językowej Na Potrzeby Glottodydaktyki I Transladydaktykiunclassified
“…Cirit (2014) indicated that as learning a second language requires the development of the all the four language skills combined, designing assessments via Web tools can fulfill what the traditional assessments cannot by motivating the learners and supporting their learning with the sources reached by means of the Web 2.0 tools. Thanks to web tools, the teachers can assess their students with the use of multimedia in a different set of formats like audio, video, images, animation and graphics which enrich the materials by making them more authentic (Suvorov &Hegelheimer, 2014).In their study, Gray et al (2012) explored the Australian academics' assessment of students' web 2.0 activities. The results suggested that other than a few challenges and risks, the academics generally found the assessment with web 2.0 tools necessary and valuable.…”
Section: Tablementioning
confidence: 99%
“…Language ability involved in the ILST and the MMST was described from the interactionalist perspective of construct definition (Chapelle, 1998). The detailed construct analysis is indispensable for investigating interactional authenticity due to the complex construct these innovative assessment tasks measure (Frost, Elder, & Wigglesworth, 2012;Plakans, 2013;Suvorov & Hegelheimer, 2013;Yu, 2013). The elicited language ability of the ILST and the MMST was compared.…”
Section: Research Questionsmentioning
confidence: 99%